Phase shift on reflection from polystyrene colloidal photonic crystal film on hydrogel surface - T. Rutirawut (2018)
© 2015 SPIE. The phase shift on reflection from the colloidal photonic crystal film was measured by the Fabry-Pérot resonant cavity along the cross-section of the photonic crystal film without additional optical parts. The wet colloidal photonic crystal film was fabricated by dip-coating an agarose-gel-coated glass substrate into a suspension containing monodisperse polystyrene nanospheres with the diameter about 188 nm. The ordered structure of monodisperse spheres in the wet film on hydrogel contributed the reflection stopband of photonic crystals together with Fabry-Pérot interference fringes of this uniform wet film over the entire visible region. The spectrum of reflectance was observed under the reflected microscope with the optical fiber spectrometer. The analyzed experimental results show the thickness of film about 20 μm and the photonic stopband peak at ∼470 nm. The variation of phase shift values between both edges of the peak varies from 0.07π to 0.88π which is in range of 0 to π as reported by other works. Moreover, these extracted optical properties are slightly changed due to the gradual water evaporation of the wet film. This stopband peak of photonic crystal is shifted to a shorter wavelength due to the more packing of nanospheres after drying.